Exposure to oral bisphosphonates and risk of cancer - Cardwell, Chris R. (2012)
Recently oral bisphosphonate use has increased markedly in the United States and elsewhere. Little is known about cancer risks associated with these drugs. A few studies have observed associations between bisphosphonates and the risk of breast, colorectal and esophageal cancer. However, the risk of all cancer and the risk of other cancers have not been investigated. In this study we examined the risk of all cancer and site specific cancers in individuals taking bisphosphonates. Data were extracted from the UK General Practice Research Database to compare site-specific cancer incidence in a cohort of oral bisphosphonate users and a control cohort. Hazard ratios were calculated using Cox regression modelling. The bisphosphonate and control cohort contained 41,826 participants (mean age 70, 81% female). Overall, the bisphosphonate cohort compared with the control cohort had a reduced risk of all cancer after any bisphosphonate usage (HR=0.87, 95% CI 0.82, 0.92). In the bisphosphonate cohort, compared with the control cohort, there was no evidence of a difference in the risk of lung (HR=1.03, 95% CI 0.88, 1.20) or prostate cancer (HR=0.86, 95%CI 0.67, 1.09) but breast (HR= 0.71, 95% CI 0.62, 0.81) and colorectal cancer (HR=0.74, 95% CI, 0.60–0.91) were both reduced. Our findings indicate that bisphosphonates do not appear to increase cancer risk. Although reductions in breast and colorectal cancer incidence were observed in bisphosphonate users it is unclear, particularly for breast cancer, to what extent confounding by low bone density may explain the association.